Предмет: Алгебра, автор: gorunovdima27

(X-2)^2+(x-3)^2=2x^2

Ответы

Автор ответа: gulerismaylova
0

 {x}^{2}  - 4x + 4 +  {x}^{2}  - 6x + 9 =  {2x}^{2}  \\   {2x}^{2}  -  {2x}^{2}  - 4x - 6x + 4 + 9 = 0 \\  - 10x + 13 = 0 \\  - 10x =  - 13 \\ x =  1\frac{3}{10}

Удачииииииииии

Автор ответа: PikSurok
0

Ответ: x=1,3

Объяснение:

(x-2)^2+(x-3)^2=2x^2

(x-2)(x-2)+(x-3)(x-3)=2x^2

x^2-2x-2x+4+x^2-3x-3x+9=2x^2

x^2-4x+4+x^2-6x+9=2x^2

2x^2-10x+13=2x^2

2x^2-10x+13-2x^2=0

-10x+13=0

-10x=-13/ *(-1)

10x=13

x=13/10

x=1,3

Похожие вопросы
Предмет: Русский язык, автор: dasha2009889999999